Pengembangan Sistem Informasi Pengolahahan Data Guru dan Pegawai pada SMA Negeri 1 Tasifeto Barat Berbasis Website - Stefanus Lau Manek; Yoseph Pius Kurniawan Kelen; Krisantus Jumarto Tey Seran; Patricia Gertrudis Manek (Saintek Lahan Kering, 2022)
Being a formal education institution, a school must have information to be shared to public. Such information could be new school year students enrollment, general situation of the school, school activities, students, teachers and administration staff's personal data. Up to this moment, school information is still conventionally publicly announced, both from mouth to mouth and by writing it on an announcement board. Such condition will positively impact in the delay of the information being shared. This situation still exists at West Tasifeto State Senior High School One which is considered one of the best schools located on the border of Indonesia – Timor Leste. Apart from the information sharing mentioned above, teachers and administration staff data processing is still manually handled by means of typing it on paper which mostly have bad effects on finding whenever needed. In this research, we developed an information system to share information and the data processing of teachers and administration staff in the form of website, to ease school data management. We believe that the existence of such media is able to process teachers and administration staff data, teachers attendance list management, school scheduling, and other school information. A Prototype Model is utilized in developing this website. The website-based information system at West Tasifeto State Senior High School One is believed to assist with the school information spreading to public, especially to the remote community, residing the border of Indonesia and Timor Leste. Anybody seeking the school information just easily logging on to the school Website and they can straightly find it without having to come to school.